Progress of Yoghurt Taste Characteristics Perception, Formation Process and Analysis and Evaluation Methods - Lin SHI; Wei JIA; Rong ZHANG; Li ZHANG (Shipin gongye ke-ji)
The scale of the yogurt market is growing rapidly, and the personalized taste and nutritional precision are the main development trends. It is an important way to improve and regulate yogurt taste quality to establish a high-throughput flavor detection method and analyze the effects of protein degradation, carbohydrate metabolism and lipid decomposition on yogurt taste characteristics during fermentation. The main taste perception processes of sour, sweet, bitter, fresh and salty yogurt are reviewed in this paper. By introducing the metabolism of protein, fat and carbohydrate, the source of the main flavor material base of yogurt is discussed. The research progress of sensory evaluation, electronic tongue, near infrared spectroscopy and chromatography-mass spectrometry in the identification and taste evaluation of yoghurt is discussed. This review can provide important scientific basis and data support for the precise control of yogurt taste quality and intelligent manufacturing, and help the high-quality development of dairy industry chain.